Morphology and molecular data reveal the presence of two new species under Rhamdia quelen (Quoy & Gaimard, 1824) (Siluriformes: Heptapteridae) species complex - Angrizani, Rafael C.; Malabarba, Luiz R. (Zootaxa, 2018)
The eustatic movements triggered by glaciations during the Quaternary have shaped the landscape of Brazilian Atlantic Coast. Cyclic sea-level changes either isolated or connected freshwater fish populations, impacting their distribution and diversification. Rhamdia quelen has been widely recorded from the Brazilian Atlantic Coastal rivers, but it is also considered a species complex. A phylogeographic study carried out using three molecular markers of mtDNA and one of nDNA in the populations of Rhamdia from the hydrographic basins of Southern Atlantic Coast of Brazil recovered three evolutionarily distinct groups: one represented by the populations found in lowlands of all studied watersheds; the second group composed of populations found in the upper tributaries of the rio Araranguá, rio Mampituba and rio Tramandaí; and a third group found exclusively in the upper portions of rio Tubarão. The genetic divergences among these three lineages of Rhamdia is discussed according to sea level changes in the Quaternary. Two new species of Rhamdia are diagnosed and described based on morphological and molecular evidence.